Case Report: Pityriasis Rosea-Like Eruption Following COVID-19 Vaccination - Leerunyakul, Kanchana; Pakornphadungsit, Kallapan; Suchonwanit, Poonkiat (Frontiers in Medicine, 2021)
Vaccination is one of the cornerstones in the efforts towards ending the coronavirus disease 2019 (COVID-19) pandemic. However, several adverse effects of COVID-19 vaccination have been identified. Pityriasis rosea (PR)-like eruption is a rare cutaneous complication of immunization. To the best of our knowledge, there have been no reports of PR-like eruptions following inoculation with Oxford/AstraZeneca ChAdOx1 nCoV-19 (AZD1222) vaccine. Here, we described a case of PR-like eruption that developed 14 days after Oxford/AstraZeneca vaccination in a 52-year-old Thai woman with glioblastoma. Treatment with topical 0.1% triamcinolone acetonide twice per day showed partial response after seven days. Despite this rare complication, our report highlights that the presence of PR-like eruption is not a contraindication for subsequent vaccinations.